A two-dimensional grouting model considering hydromechanical coupling and fracturing for fractured rock mass - Yan, Chengzeng; Tong, Yao; Luo, Zhiqiang; Ke, Wenhui; Wang, Gang (Engineering analysis with boundary elements, 2021)
A two-dimensional grouting model considering hydromechanical coupling and fracturing in fractured rock is proposed and implemented in an GPU parallel multiphysics finite element-discrete element software named MultiFracs. The model can simulate the grout flows in existing and induced fractures in the rock media. The fracture network is represented by broken joint elements, which is updated to simulate fracture initiation and propagation during grouting. Therefore, both the hydromechanical coupling effect and rock fracturing are considered in the grouting model. A single-fracture grouting example is presented to verify the grouting model. Finally, the model is used to simulate the grouting process in a rock mass with a complex fracture network. The effects of grout yield stress, amount of injection holes, injection pressure, aperture, and especially hydromechanical coupling on grout penetration are studied. The results show that the grouting model can simulate the interaction between grouting-induced fractures and pre-existed fractures.